THE EFFECT OF E-SERVICE QUALITY, PROMOTIONS AND PRICE ON PURCHASE DECISIONS ON THE LAZADA PLATFORM IN THE JABODETABEK AREA - Wigar Ramadhan Anargya Widodo; Ardiansyah; Rahmi Utami (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study examines the influence of E-Service Quality, Promotion, and Price on Purchase Decisions on the Lazada platform in the Greater Jakarta (Jabodetabek) area. Data were collected from 385 respondents who had previously made purchases through Lazada using a questionnaire. The study utilized primary and secondary data and was analyzed using SPSS. The results of the t-test indicate that E-Service Quality, Promotion, and Price each have a significant positive effect on Purchase Decisions. Better service quality enhances consumer confidence in making transactions, while effective promotional activities encourage purchase intentions. Competitive and appropriate pricing also contributes positively to purchasing decisions. Among the independent variables, Promotion emerged as the most dominant factor influencing Purchase Decisions. The coefficient of determination (R²) shows that 64% of Purchase Decisions are explained by the variables examined in this study.